Preliminary analysis of legal obstacles and incentives to the development of low-head hydroelectric power in the northeastern United States (Energy Law Inst., Concord, NH (USA). Franklin Pierce Law Center, 1980)
A preliminary analysis of the legal obstacles and incentives to the development of the low-head hydroelectric potential of the 19 northeastern US (Maine, New Hampshire, Vermont, Massachusetts, Rhode Island, Connecticut, New York, New Jersey, Pennsylvania, Ohio, Indiana, Michigan, Illinois, Wisconsin, Kentucky, Maryland, Delaware, Virginia, and West Virginia) is presented. The statutes and case laws of the 19 states and the Federal government which affect developers of small dams are stressed. The legal uncertainty which confronts the developer of small dams and the regulatory burden to which the developer may be subjected once the uncertainty is resolved are emphasized.